The Construction of Habib Rizieq Shihab's Political Islamic Thought in the Post-Reform Indonesian Context - Hidayat, Dede; Truna, Dody S.; Rahman, Mohammad Taufiq; Muhyidin, Asep (Hanifiya: Jurnal Studi Agama-Agama, 2023)
This article describes a religious movement figure in post-Reformation Indonesia (1998), namely Habib Rizieq Shihab, who had a mass organization considered radical, namely the Islamic Defenders Front. This article answers the accusation that Shihab was anti-state politics, anti-Pancasila, anti-the Republic of Indonesia, and was intolerant of anyone different from the movement he had led. This study uses the content analysis method, namely analyzing the ideas in Shihab's writings and lectures to reveal his Islamic political ideology. This study found that Shihab's theology was Ashary and Shafiy Sunni with Alawiy Tareqat order. The Muslim Brotherhood influenced Shihab's thoughts and Al-Maududi's ideas, namely, aspiring to an Islamic state or formalizing religious constitutional law into a condition known as Islamic law. At the local level, Shihab was influenced by the local scholar M. Natsir. However, Shihab's political Islamic thought results gave distinctive features and differed from the existing typology. Shihab accepted Pancasila as the basis of the state. However, the "Shari'ated Indonesia" concept was a theistic concept perceived as implementing the Islamic caliphate vision and mission and the reincarnation of the 1945 Jakarta Charter Pancasila.